Melatonin—Angel of plant growth regulation and protection - Huanyu Cai; Jie Li; Jun Li; Huailong Teng (Advanced Agrochem)
Melatonin (N-Acetyl-5-methoxytryptamine), an endogenously synthesized indoleamine, exerts pleiotropic effects in plant physiology by interacting with other phytohormones, thereby synergistically regulating plant growth, development, and stress responses. Recent research has also indicated that melatonin derivatives could be further developed as promising antifungal candidates. Given the significant roles of melatonin, considerable efforts have been devoted to studying its potent functions and underlying mechanisms. This review outlines recent advancements in understanding the roles of melatonin in regulating plant growth and its potential synergistic interactions with pathogens. Additionally, we present our perspectives aimed at elucidating the antifungal mechanisms of melatonin and its derivatives, which could facilitate the development of naturally sourced fungicides and offer innovative strategies for pesticide discovery.